1978
DOI: 10.1111/j.1399-0039.1978.tb01322.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA Antigens in Patients with Psoriasis

Abstract: Tissue typing was performed on lymphocytes of 46 Jewish patients with psoriasis vulgaris. HLA B13, B17, B37 and Cw6 were found increased. It is suggested that the increase in the B and C locus antigens is inter-related and may determine the genetic predisposition for the development of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…Whilst some studies in the USA [14,17] indicated an increased frequency of HLA-Bwl6, the increase found in our ethnic group was equivocal because it did not result significant after correction, as suggested by Svejgaard et al [22] in a large study of European Caucasoids. Present findings also confirmed a striking association of psoriasis and Cw6, demonstrated by other authors [8,17,25], This was due to the high linkage disequilibrium ofCw6 with B13, B17 and B37 [3a], indicating that association of B locus antigens with psoriasis are secondary to the association of Cw6 with the disease.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Whilst some studies in the USA [14,17] indicated an increased frequency of HLA-Bwl6, the increase found in our ethnic group was equivocal because it did not result significant after correction, as suggested by Svejgaard et al [22] in a large study of European Caucasoids. Present findings also confirmed a striking association of psoriasis and Cw6, demonstrated by other authors [8,17,25], This was due to the high linkage disequilibrium ofCw6 with B13, B17 and B37 [3a], indicating that association of B locus antigens with psoriasis are secondary to the association of Cw6 with the disease.…”
Section: Discussionsupporting
confidence: 77%
“…The increase in the frequency of B13 and B17 antigens shown in an Italian population (Apulia Region) of psoriatic patients agreed with the findings in other populations [8,11,20,22,28], confirming a wide asso ciation between HLA antigens and psoriasis.The question of disturbed frequency of other HLA antigens was more uncertain. Whilst some studies in the USA [14,17] indicated an increased frequency of HLA-Bwl6, the increase found in our ethnic group was equivocal because it did not result significant after correction, as suggested by Svejgaard et al [22] in a large study of European Caucasoids.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The association of the disease with Cw6 is more significant in non-Ashkenazi than in Ashkenazi patients (x2 = 11.7 vs x2 = 2.8, respectively), while the frequency of Cw6 among healthy individuals is similar in both subpopulations. In a previous study, Gazit et al (1978) also reported an increase in Cw6 among Jewish psoriatic patients. PSV has also been reported to be associated with DR7 (Marcusson et al 1981, Tiwari et al 1982.…”
Section: Discussionmentioning
confidence: 68%